2009
DOI: 10.1002/adem.200900061
|View full text |Cite
|
Sign up to set email alerts
|

Designing Ultrahigh Strength Steels with Good Ductility by Combining Transformation Induced Plasticity and Martensite Aging

Abstract: Steels with a high ultimate tensile strength (UTS) above 1 GPa and good ductility [total elongation (TE) of 15-20% in a tensile test] are of paramount relevance for lightweight engineering design strategies and corresponding CO 2 savings, Figure 1. [1,2] In this work, we report about a novel design approach for precipitation hardened ductile high strength martensitic and austenitic-martensitic steels (up to 1.5 GPa strength). The alloys are characterized by a low carbon content (0.01 wt% C), 9-15 wt% Mn to obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 33 publications
4
70
0
7
Order By: Relevance
“…Recently, a group of newly-developed 9-12 wt.% Mn lean maraging TRIP (transformation induced plasticity) steels with minor additions of Ni, Ti and Mo was reported to possess an excellent combination of strength and ductility (e.g. 12 wt.% Mn alloy: ultimate tensile strength (UTS): ~1.3 GPa, total elongation (TE): ~21%) [4] [5]. The authors attributed the simultaneous increase of strength and ductility upon aging to the joint effect of precipitation strengthening mechanism and TRIP mechanism of retained austenite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a group of newly-developed 9-12 wt.% Mn lean maraging TRIP (transformation induced plasticity) steels with minor additions of Ni, Ti and Mo was reported to possess an excellent combination of strength and ductility (e.g. 12 wt.% Mn alloy: ultimate tensile strength (UTS): ~1.3 GPa, total elongation (TE): ~21%) [4] [5]. The authors attributed the simultaneous increase of strength and ductility upon aging to the joint effect of precipitation strengthening mechanism and TRIP mechanism of retained austenite.…”
Section: Introductionmentioning
confidence: 99%
“…However, the characterisation of precipitates in these Fe-Mn maraging steels is a matter of debate. Initially, both atom probe tomography (APT) and local energydispersive X-ray spectroscopy (EDS) analyses revealed the precipitates were enriched in Ni, Al and Ti and it was speculated that the precipitates might be -Ni 3 (Ti,Al) phase which is the most common precipitates in conventional 18Ni maraging steels [4] [5]. However, later…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that the reverted austenite has no effect in the 4 Since the growth and coarsening equations in 9 and 13 evolve according to ∼t 1/2 and ∼t 1/3 , respectively, a sharp variation in r p can be observed at the transition when .…”
Section: Strengthening Mechanisms In Maraging Steelsmentioning
confidence: 99%
“…Schober et al [53] observed in Fe Ni Al Mo the formation of -NiAl. 2 Small additions of Ti partition into NiAl forming Ni 2 AlTi in Fe Ni Mn Al Ti when nickel content is low (≤4 wt%) [4,25,54], whilst very low amounts of Mn atoms partition into the precipitates. No Mo partitioning to NiAl and its variants in 1 Although BCC-Cu is not an intermetallic phase, the same evolution descriptions will be adopted for all precipitates.…”
Section: Compositional Effects On Intermetallic Formationmentioning
confidence: 99%
See 1 more Smart Citation